Analysis of air quality monitoring in Brazil - Vormittag, Evangelina da Motta P. A. de Araújo; Cirqueira, Samirys Sara Rodrigues; Wicher Neto, Hélio; Saldiva, Paulo Hilário N. (Estudos Avançados, 2021)
This article describes the current conditions of the air quality monitoring network in Brazil. The results reveal that only ten states and the Federal District carry out the monitoring through 371 active stations - 80% in the Southeast region. Other relevant information include: (i) 41.2% of the national stations are private - in the state of Rio de Janeiro they represent 60% of the its total of stations, while in the state of São Paulo, 100% of the stations are public; (ii) MP10 is the most monitored pollutant in 62.8% of stations and MP2.5 in only 25.9% of them; and, (iii) the communication of monitoring data in real time to the population occurs in five states. Thirty years after its creation, the National Air Quality Network, is incomplete and insufficiently implemented, preventing adequate air quality management by environmental agencies.